Canyons - Hanson, Erik A.; Nash, Geoffrey H. (New York : Chelsea House, 2007)
Profiles canyons around the world including the Grand Canyon, the Columbia River Gorge, Fish River Canyon, and and Monterey Canyon; and describes how and when they were formed, how the landscape has changed over time, and the contribution of each to the environment.
The Grand Canyon, Northern Arizona, the United States -- The Columbia River Gorge, Northern Oregon and Southern Washington, the United States -- The three gorges of the Yangtze River, Hubei Province and Sichuan Province, Southern China -- Peonera canyon, Aragón Province, Northeastern Spain -- Windjana Gorge, the Napier Range, Northwestern Australia -- Monterey Canyon, Monterey Bay, Central California, the United States -- Zion Canyon, Southwestern Utah, the United States -- Fish River Canyon, Namibian Highland, Southern Mabibia -- Chaco Canyon, Northwestern New Mexico, the United States -- Canyon Diablo and Meteor Crater, Northern Arizona, the United States.
Description based on print version record.
Includes bibliographical references (p. 190-198) and index.
Keywords: Plate tectonics -- Juvenile literature; Canyons -- Juvenile literature; Plate tectonics; Canyons; Electronic books; Electronic books